Pulsate '08 : there's more in you than you think - Lim, Wen Ying (2009)
This paper presents the “Pulsate ’08” campaign, a collaboration between the United World College (UWC) National Committee of Singapore and Team Pen N’ Paper, a team of four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The UWC is a global education movement aimed at providing education and foster international understanding and peace. The UWC is represented by National Committees, and the committees offer scholarships that allow holders to study in one of their colleges. The campaign aims to increase awareness of the UWC scholarship, to share the UWC experience with the target audience, to create interest in the scholarship in 2008 and attract more applicants, and to create sustainable contacts and avenues for publicizing the UWC scholarship. The objectives are achieved through school presentations, a one-day workshop, a speech contest, and a constant online presence in the form of a blog and forum. Through this campaign, the team has managed to promote the scholarship to the 162 secondary schools in Singapore, personally visit 12 schools and expose more than 3000 students to the scholarship.